2012
DOI: 10.1007/s10096-012-1690-y
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole for chronic pulmonary aspergillosis: a prospective multicenter trial

Abstract: Early evidence suggests the efficacy of voriconazole for chronic pulmonary aspergillosis (CPA). We conducted a prospective, open, multicenter trial to evaluate the efficacy and safety of voriconazole for proven CPA in minimally or non-immunocompromised patients. Patients had CPA confirmed by chest computed tomography (CT) and/or endoscopy, positive Aspergillus culture from a respiratory sample, and positive serologic test for Aspergillus precipitins. Patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
2
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 27 publications
5
95
2
10
Order By: Relevance
“…Oral triazole therapy for CCPA is now considered the standard of care. Oral voriconazole is also effective for CCPA with an acceptable tolerability in several studies as primary therapy (SoR A and QoE II) or after itraconazole (either because of failure or intolerance) (SoR A and QoE II) [15,30,[89][90][91][92]. A retrospective cohort study supports the evidence that oral posaconazole may be a potential alternative treatment (SoR B and QoE II) [59].…”
Section: Treatment and Follow-upmentioning
confidence: 53%
See 3 more Smart Citations
“…Oral triazole therapy for CCPA is now considered the standard of care. Oral voriconazole is also effective for CCPA with an acceptable tolerability in several studies as primary therapy (SoR A and QoE II) or after itraconazole (either because of failure or intolerance) (SoR A and QoE II) [15,30,[89][90][91][92]. A retrospective cohort study supports the evidence that oral posaconazole may be a potential alternative treatment (SoR B and QoE II) [59].…”
Section: Treatment and Follow-upmentioning
confidence: 53%
“…Some cases of SAIA have responded to long-term oral itraconazole in some cohort studies [31,86,87,93,94]. A prospective multicentre study of CPA patients treated with voriconazole confirmed data obtained in a preliminary study showing that voriconazole efficacy was significantly greater in patients with SAIA than in those with CCPA [15,90,95].…”
Section: Treatment and Follow-upmentioning
confidence: 72%
See 2 more Smart Citations
“…Optimal treatment of pulmonary aspergillosis complicated with noncavitary lung tumor has not yet been established; whether antifungal treatment is overtreatment remains controversial. Antifungal treatment including itraconazole or voriconazole have efficacy for CPA and cavitary CPA (20)(21)(22)(23)(24). However, no studies have evaluated the significance of antifungal treatment for aspergillosis coexisting with lung carcinomas.…”
Section: Discussionmentioning
confidence: 99%